Ayurvedic vs. Conventional Nutritional Therapy Including Low-FODMAP Diet for Patients With Irritable Bowel Syndrome—A Randomized Controlled Trial - Jeitler, Michael; Wottke, Till; Schumann, Dania; Puerto Valencia, Laura M.; Michalsen, Andreas; Steckhan, Nico; Mittwede, Martin; Stapelfeldt, Elmar; Koppold-Liebscher, Daniela; Cramer, Holger; Wischnewsky, Manfred; Murthy, Vijayendra; et al. (Frontiers in Medicine, 2021)
Aims: To compare the effects of Ayurvedic and conventional nutritional therapy in patients with irritable bowel syndrome (IBS). Methods: Sixty-nine patients with IBS were randomized to Ayurvedic (n=35) or conventional nutritional therapy according to the recommendations of the German Nutrition Society including the low-FODMAP diet (n=34). Study visits took place at baseline and after 1, 3 and 6 months. The primary outcome was IBS symptom severity (IBS-SSS) after 3 months; secondary outcomes included stress (CPSS), anxiety and depression (HADS), well-being (WHO-5) and IBS-specific quality of life (IBS-QOL). A repeated measures general linear model (GLM) for intent-to-treat-analyses was applied in this explorative study. Results: After 3 months, estimated marginal means for IBS-SSS reductions were 123.8 (95% confidence interval [95%CI]=92.8-154.9; p<0.001) in the Ayurvedic and 72.7 (95%CI=38.8-106.7; p<0.001) in the conventional group. The IBS-SSS reduction was significantly higher in the Ayurveda group compared to the conventional therapy group (estimated marginal mean=51.1; 95%CI=3.8-98.5; p=0.035) and clinically meaningful. 68% of the variance in IBS-SSS reduction after 3 months can be explained by treatment, 6.5% by patients’ expectations for their therapies and 23.4% by IBS-SSS at pre-intervention. Both therapies are equivalent in their contribution to the outcome variance. The higher the IBS-SSS score at pre-intervention and the larger the patients’ expectations, the greater the IBS-SSS reduction. There were no significant group differences in any secondary outcome measures. No serious adverse events occurred in either group. Conclusion: Patients with IBS seem to benefit significantly from Ayurvedic or conventional nutritional therapy. The results warrant further studies with longer-term follow-ups and larger sample sizes. Trial Registration: NCT03019861 (https://clinicaltrials.gov/ct2/show/NCT03019861)